5-a-day fruit and vegetable food product labels: reduced fruit and vegetable consumption following an exaggerated compared to a modest label - K. M. Appleton; H. J. Pidgeon (BMC, 2018)
Abstract Background Food product labels based on the WHO 5-a-day fruit and vegetable (FV) message are becoming increasingly common, but these labels may impact negatively on complementary or subsequent FV consumption. This study aimed to investigate the impact of a '3 of your 5-a-day' versus a '1 of your 5-a-day' smoothie product label on subsequent FV consumption. Methods Using an acute experimental design, 194 participants (90 males, 104 females) were randomised to consume a smoothie labelled as either '3 of your 5-a-day' (N = 97) or '1 of your 5-a-day' (N = 97) in full, following a usual breakfast. Subsequent FV consumption was measured for the rest of the day using 24-h recall. Usual FV consumption was also assessed via 24-h recall for the day before the study. Results Regression analyses revealed a significantly lower subsequent FV consumption following smoothies displaying the '3 of your 5-a-day' label compared to the '1 of your 5-a-day' label (Beta = − 0.15, p = 0.04). Secondary analyses revealed these effects to be driven mainly by changes to consumption in usual high FV consumers, in females and in vegetable as opposed to fruit consumption. Conclusions These findings demonstrate a role for label information in food intake, and the potential negative impacts of an exaggerated food product label on healthy food consumption and healthy dietary profiles.